Coaches’ Preferences for Continuing Coaching Education in South Africa - Kubayi, Alliance (J Hum Kinet, 2016)
The purpose of this study was to examine coaches’ preferences for continuing coaching education. The sample consisted of 122 male and 102 female coaches from the Gauteng Province of South Africa who were purposively recruited to participate in this study. The results of this study showed that the coaches wanted to learn more about motivational techniques, advanced instructional drills, advanced first aid, goal setting, character building and conditioning drills. The results further indicated that sport coaches would be more likely to continue their coaching education if they had a desire to coach at a high level, if topics were relevant and if courses were in line with league requirements and were available online. The practical implications of the findings for the development of coaching education programmes in South Africa were discussed.